Enhanced CO2 electrolysis with a SrTiO3 cathode through a dual doping strategy - Ye, L.; Hu, X.; Wang, X.; Chen, F.; Tang, D.; Dong, Dehua; Xie, K. (R S C Publications, 2019)
The significant role of perovskite defect chemistry through A-site doping of strontium titanate with lanthanum for CO2 electrolysis properties is demonstrated. Here we present a dual strategy of A-site deficiency and promoting adsorption/activation by making use of redox active dopants such as Mn/Cr linked to oxygen vacancies to facilitate CO2 reduction at perovskite titanate cathode surfaces. Solid oxide electrolysers based on oxygen-excess La0.2Sr0.8Ti0.9Mn(Cr)0.1O3+d, A-site deficient (La0.2Sr0.8)0.9Ti0.9Mn(Cr)0.1O3-d and undoped La0.2Sr0.8Ti1.0O3+d cathodes are evaluated. In situ infrared spectroscopy reveals that the adsorbed and activated CO2 adopts an intermediate chemical state between a carbon dioxide molecule and a carbonate ion. The double strategy leads to optimal performance being observed after 100 h of high-temperature operation and 3 redox cycles, suggesting a promising cathode material for CO2 electrolysis.